2021
DOI: 10.1038/s41398-021-01486-5
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk scoring to assess genetic overlap and protective factors influencing posttraumatic stress, depression, and chronic pain after motor vehicle collision trauma

Abstract: Posttraumatic stress (PTS), depressive symptoms (DS), and musculoskeletal pain (MSP) are common sequelae of trauma exposure. Although these adverse posttraumatic neuropsychiatric sequelae (APNS) are often studied separately, clinical comorbidity is high. In a cohort of European American motor vehicle collision (MVC) trauma survivors (n = 781), substantial PTS (≥33, IES-R), DS (≥26, CES-D), and MSP (≥4, 0–10 NRS) were identified via a 6-month survey. Genetic risk was estimated using polygenic risk scores (PRSs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 83 publications
0
13
2
1
Order By: Relevance
“…Our findings are consistent with suggestions that early clinical ratings of pain and disability or other patient-reported psychological or stress-related screening tools could help identify those most at risk of PTSI after MSI. 4 , 9 , 11 Further research is needed on preexisting mental health conditions or exposures to psychological trauma and risk of developing PTSI. Previous mental health problems may lower resilience in the face of MSI or other trauma as well as increase the risk of poor PTSI outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with suggestions that early clinical ratings of pain and disability or other patient-reported psychological or stress-related screening tools could help identify those most at risk of PTSI after MSI. 4 , 9 , 11 Further research is needed on preexisting mental health conditions or exposures to psychological trauma and risk of developing PTSI. Previous mental health problems may lower resilience in the face of MSI or other trauma as well as increase the risk of poor PTSI outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified that acute pain severity and associated psychological symptoms, such as catastrophizing, fear avoidance, low self-efficacy, and emotional problems, are also associated with development of PTSI symptoms 6–10 . These clinical characteristics are known to be influenced by physiological, social, and cultural factors 11 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Over the past decade however, large-scale genomewide association studies (GWAS) have made inroads towards elucidating the biological pathways and complex traits contributing to a wide range of conditions such as neurological, psychiatric & cardiometabolic disorders. 2 While such studies have provided evidence for genetically supported therapeutic targets & mechanisms, 3,4 the application of statistical genetics methods to musculoskeletal [5][6][7][8][9][10][11][12][13][14][15][16][17] and chronic pain conditions [18][19][20][21][22][23][24][25] as a strategy towards disentangling their causal mechanisms requires further comprehensive & concerted effort.…”
Section: Introductionmentioning
confidence: 99%
“…Polygenic scores predicted recent snoring and probable obstructive sleep apnea in an independent Australian sample (n = 8000). A potential causal relationship between high BMI and snoring was suggested based on Mendelian randomization analysis results.Several studies have compared PRSs by applying genetic analysis of speci c phenotypes to other independent group data[19][20][21][22][23][24]. According to a previous study that assessed PRSs for coronary artery disease and type 2 diabetes as predictive factors for cardiovascular (CV) mortality[21], both CAD PRS (low vs. very high genetic risk groups, CAD PRS hazard ratio [HR] 2.61 [2.02-3.36]) and T2DM PRS (HR 2.08 [1.58-2.73]) were signi cantly correlated with CV mortality risk.…”
mentioning
confidence: 99%